2005
DOI: 10.1128/jb.187.8.2662-2672.2005
|View full text |Cite
|
Sign up to set email alerts
|

TheBacillus subtilisSinR and RapA Developmental Regulators Are Responsible for Inhibition of Spore Development by Alcohol

Abstract: Even though there is a large body of information concerning the harmful effects of alcohol on different organisms, the mechanism(s) that affects developmental programs, at a single-cell level, has not been clearly identified. In this respect, the spore-forming bacterium Bacillus subtilis constitutes an excellent model to study universal questions of cell fate, cell differentiation, and morphogenesis. Here, we demonstrate that treatment with subinhibitory concentrations of alcohol that did not affect vegetative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…As indicated earlier, one important requirement for the onset of the sporulation is that sporulation-committed cells induce the expression of spo0A (8,10,23,24,25). Therefore, the level of spo0A expression seems to be a valid tool to determine whether a C. perfringens culture has initiated the formation of spores beyond stage zero.…”
Section: Vol 74 2006 Notes 3653mentioning
confidence: 90%
“…As indicated earlier, one important requirement for the onset of the sporulation is that sporulation-committed cells induce the expression of spo0A (8,10,23,24,25). Therefore, the level of spo0A expression seems to be a valid tool to determine whether a C. perfringens culture has initiated the formation of spores beyond stage zero.…”
Section: Vol 74 2006 Notes 3653mentioning
confidence: 90%
“…For sporulation efficiency, B. subtilis strains were grown in SM for 20 h and then treated with 10% CHCl 3 for 15 min before being plated as previously described (2). Transformation of B. subtilis, to obtain isogenic derivates of the parental strains, was carried out as previously described (18). ␤-Galactosidase assays from B. subtilis strains harboring lacZ fusions were assayed as described previously and the specific activity was expressed in Miller units (2).…”
Section: Methodsmentioning
confidence: 99%
“…SinR is a regulator involved in late growth processes and biofilm formation (Kearns et al, 2005). These data suggested that the two regulators RapA and SinR were solely responsible for the observed blockage of sporulation by ethanol stress in the B. subtilis wild type, neither s B nor the general stress genes were considered to be involved in the inhibitory effect of alcohol stress on sporulation (Gottig et al, 2005).…”
Section: Ethanol Stress and Impairment Of Sporulation Specific Transcmentioning
confidence: 99%